Knowledge-sharing efforts and employee creative behavior: the invigorating roles of passion for work, time sufficiency and procedural justice - De Clercq, D.; Pereira, R. (Journal of Knowledge Management, 2020)
Purpose: Drawing from the conservation of resources theory, this study aims to investigate the relationship between employees’ knowledge-sharing efforts and creative behaviors; particularly, it addresses how this relationship may be invigorated by three resources that operate at individual (passion for work), job (time sufficiency) and organizational (procedural justice) levels. Design/methodology/approach: Quantitative data were collected through a survey administered to employees in a banking organization in Mozambique. Findings: The usefulness of knowledge-sharing efforts for stimulating creative behavior is greater when employees feel passionate about work, have sufficient time to complete their job tasks and perceive that organizational decision-making is fair. Practical implications: The results inform organizations about the circumstances in which the application of employees’ collective knowledge bases, derived from their peer interactions, to the generation of novel solutions for problem situations is more likely to materialize. Originality/value: By detailing the interactive routes by which knowledge-sharing efforts and distinct resources (passion for work, time sufficiency and procedural justice) promote employee creative behavior, this study extends prior research that has focused on the direct influences of these resources on knowledge sharing and creative work outcomes. It pinpoints the circumstances in which intra-organizational knowledge exchange can generate the greatest value, in terms of enhancing creativity.